Fluid-solid conjugate heat transfer modelling using weakly compressible smoothed particle hydrodynamics - Ng, Khai Ching; Ng, Y.L.; Sheu, Tony Wen Hann; Mukhtar, Azfarizal (Elsevier, 2019)
To date, the Smoothed Particle Hydrodynamics (SPH) method which is mesh-less and fully Lagrangian in nature has been mainly applied in solving solid heat conduction problem and flow convection problem separately. In the current work, we have implemented the Weakly Compressible Smoothed Particle Hydrodynamics (WCSPH) method to solve internal flow problem involving fluid-solid Conjugate Heat Transfer (CHT). In order to ensure heat flux continuity across the interface separating two different materials, the harmonic mean value of thermal conductivities was adopted when modelling the heat transfer between fluid and solid bodies. On the modelling of non-isothermal hydrodynamically fully-developed channel flow, the Dirichlet inlet temperature boundary condition was implemented without having to build a separate temperature reset zone as proposed in the open literature. From the current study, we have found that the particle shifting algorithm is efficient to address the tensile instability problem encountered when simulating flow at high Reynolds number. The WCSPH results were compared against the established analytical and numerical solutions and good agreement was found. The idea of extending the WCSPH method to simulate the flow and heat transfer in parallel-flow and counter-flow heat exchangers was pursued in the current study as well.